Structural Transformation of Occupation Employment - Georg Duernecker; Berthold Herrendorf (Center for Economic Studies and ifo Institute (CESifo), 2021)
We use census data to show that structural transformation reflects a fundamental reallocation of labor from goods to services, instead of a relabelling that occurs when goods-producing firms outsource their in-house service production. The novelty of our approach is that it categorizes labor by occupations, which are invariant to outsourcing. We find that the reallocation of labor from goods-producing to service-producing occupations is a robust feature in censuses from around the world and different time periods. To understand the underlying forces, we propose a tractable model in which uneven occupation-specific technological change generates structural transformation of occupation employment.
Keywords: O11; O14; 330; biased technological change; occupations; outsourcing; structural transformation